A method for drawing vertical curve in longitudinal profile in road project. Issue 368 (3rd September 2019) - İnce, Hüseyin; Erdem, Nuri
Abstract : In road projects, there is a difficulty in drawing tangent points of the calculated vertical curve, turning point and intermediate points due to horizontal and vertical scale differences. This problem is brought about by the fact that proportional relationship between the two different scales is not known for a length with a certain slope in longitudinal profile. This study proposes a method to eliminate this problem. It also gives an example and discusses the findings.